Neurocognitive aspects of ketamine and esketamine on subjects with treatment-resistant depression: A comparative, randomized and double-blind study - Araújo-de-Freitas, Lucas; Santos-Lima, Cassio; Mendonça-Filho, Euclides; Vieira, Flávia; França, Ricardo J A F; Magnavita, Guilherme; Cardoso, Tanise L; Correia-Melo, Fernanda S; Leal, Gustavo C; Jesus-Nunes, Ana Paula; Souza-Marques, Breno; Marback, Roberta; et al. (Psychiatry research, 2021)
•Ketamine and Esketamine improve cognition in depression.•Ketamine and Esketamine have similar effect on cognition in depression.•Low doses of Ketamine and Esketamine are cognitively safe in depression. The objective of this study is to evaluate cognition in patients using either ketamine or esketamine to treat TRD. We also evaluate if both ketamine and esketamine as one group influence cognition in patients with TRD. Fifty-four patients with TRD were infused with either ketamine or esketamine and were assessed at three time points: baseline, 24 h, and 7 days after infusion. We applied neuropsychological tests to evaluate executive functions, processing speed, short term memory, and auditory-verbal episodic memory. There is no cognitive difference between ketamine and esketamine, with the exception of one variable. When considered as one group, ketamine and esketamine do not impair cognition; on the contrary, they improve some neuropsychological functions such as visuospatial short-term memory, executive functions, processing speed, and several measures related to episodic verbal memory. Ketamine and esketamine do not present differing cognitive effects when used in antidepressant doses to treat TRD. Furthermore, they rapidly improve many cognitive aspects of patients with TRD at 24 h after the infusion and maintain these effects for at least 7 days.